A quasi-hyperbolic discounting approach to smoking behavior - Takanori Ida (Health Economics Review, 2014)
Addiction has attracted considerable attention in health and behavioral economics, and economists have attempted to understand addiction from the viewpoint of decision making over time. This paper investigates whether two time preference parameters can successfully predict smoking status, including cigarette dependence. Both the present bias and the constant time preference parameters account for smoking behavior status and cigarette dependence.
Keywords: D81; D91; I12; 330; Smoking; Cigarette dependence; Time preference; Present bias